PTH-041 Polyp Cancers: When is Surgical Resection Needed ?. (4th June 2013) - Rameshshanker, R; King, A; Catnach, S; Cerys, S; Macfarlane, B
Abstract : Introduction: The Bowel Cancer Screening Program (BCSP) has been successful in detecting early stage bowel cancer, including polyp cancers. Most polyp cancers are not recognised as such at the index colonoscopy and are managed initially with endoscopic resection. There are histological criteria to predict high risk polyp cancers and need for further surgical resection. The decision is not always clear cut, and who to refer for surgery is difficult. A single centre experience is reported Methods: Polyp cancers detected through the BCSP at West Herts NHS Trust between August 2008 and December 2011 were identified. Endoscopy reports, polyp histology, surgical referrals and surgical histology were analysed. Results: 1334 colonoscopies were performed and 25 polyp cancers which had been managed initially with endoscopic resection were identified. Twenty four were within recto-sigmoid area, size range 1–4 cm. No polyp cancers were poorly differentiated. Patient age range was 60–74 yrs, median 66 yrs. Fourteen patients had endoscopic resection (ER) alone: thirteen remain disease free at 1 year endoscopic follow up, one patient did not attend. Of the pedunculated polyp cancers, two were Haggitt 1 (H1), four Haggitt 2 (H2 ) and three Haggitt 3 (H3). The resection margin (RM) ranged from 1.5 to 12 mm. There was tumour budding in just one, but the RM was 12 mm. No case had lympho vascular invasion (LVI). Of the sessile polyp cancers there were two Kikuchi 1 (K1), two Kikuchi 2 (K2) and one Kikuchi 3(K3). There was budding in one case, a K1 polyp, and one LVI in a K2 polyp but with 4 mm RM. The K3 polyp had budding, no LVI and RM 0.5-MRI and CT scans were negative in this patient. Eleven patients were referred for surgery post ER. Nine patients had no residual tumour. In these nine patients, polyp features dictating referral were: one H2 with budding and 0.5 mm RM, one H3 with LVI and 1 mm RM, one H3 with budding and 1 mm RM, one H3 with 0.5 mm RM, one H3 RM not clear, one H3 with 2mm RM no LVI or budding, one K2 with budding LVI and 0.5 mm RM, two K3 RM not clear. Two patients had cancer: one pT1pN1Mx (polyp cancer: H3 no budding or LVI RM 1mm) and pT1pN0Mx (polyp cancer: K2 with budding RM 0.5) Conclusion: When all three high risk histological features (budding, LVI, RM < 1mm) are absent or present a decision re surgical referral can be straightforward. Using these parameters, in our study, probably one patient more should have been referred for surgical resection, and one patient less. The decision challenge lies when just one or two parameters are present. A pessimistic view is that 82% of our patients had unnecessary surgery, an optimistic one that 18% had appropriate surgery. Age and associated morbidity are also important factors illustrating the value of the MDT in these challenging decisions Disclosure of Interest: None Declared.